Effectiveness of Notion Application to the Development of Learner Autonomy in TOEIC Learning - Huynh, Nguyen Khanh (VNU Journal of Science: Education Research; Vol 40 No 4, 2024)
Learner autonomy has received increasing attention in Vietnamese context, especially with the arising of ICT in English teaching and learning. This quantitative study aims to explore the effectiveness of Notion application to the development of learner autonomy perceived by learners. The participants include 50 university students from two TOEIC classes in HCMC, who were encouraged to use Notion app during a 2-month course. A close-ended questionnaire was adapted to collect data. The findings revealed that TOEIC learners perceived Notion app as effective in the fostering of their learning autonomy, regarding the high extent to which it helped them take charge of learning, have positive attitudes towards learning, learn cooperatively with peers, develop study skills, and build good relationships with teacher.